PENGARUH MODEL PEMBELAJARAN DAN MINAT BELAJAR TERHADAP HASIL BELAJAR SISWA PADA MATERI KESETIMBANGAN KIMIA DI SMA (JS (JURNAL SEKOLAH), 2022)
Abstract : The Effect of Learning Models and Interest in Learning on Student Learning Outcomes on Chemical Equilibrium Material in High School. This study aims to obtain information and data regarding whether or not there are differences in student learning outcomes who are taught with varied learning models and varied learning interests using the iSpring learning media on chemical equilibrium material, as well as see the interaction between student learning outcomes and student interest in learning. The population in this study were all students of class XI MIPA at SMA Negeri 1 Sei Suka, totaling five classes. The samples used in this study were two classes taken by purposive sampling. The samples in this study were class XI MPA 1 as experimental class 1 which was treated using the Problem Based Learning (PBL) model and class XI MIPA 4 which was treated with the Learning Cycle 5E model. Hypothesis testing was carried out with two- way ANOVA (two-way ANOVA) with univariate General Linear Model (GLM) with the results of research on various learning models obtained sig. 0.007 < (0.05) so that Ha is accepted and Ho is rejected, it can be concluded that there is a significant difference in the average value of student learning outcomes on the chemical equilibrium material that is taught with varied learning models. In the varied learning interests obtained sig. 0.000 < (0.05) so that Ha is accepted and Ho is rejected, it can be concluded that there is a significant difference in the average value of student learning outcomes on chemical equilibrium material taught with varied learning interests. Furthermore, on the interaction between the learning model and interest in learning, the value of sig is obtained. 0.003 < (0.05) so that Ha is accepted and Ho is rejected, it can be concluded that there is an interaction between the learning model and interest in learning on the value of student learning outcomes in the Chemical Equilibrium material.Keyword : Problem Based Learning (PBL) Model, 5E Learning Cycle Model, Interest in Learning, iSpring Media, LearningAbstrak : Pengaruh Model Pembelajaran Dan Minat Belajar Terhadap Hasil Belajar Siswa Pada Materi Kesetimbangan Kimia Di SMA. Penelitian ini bertujuan untuk mendapatkan informasi dan data mengenai ada atau tidaknya perbedaan hasil belajar siswa yang dibelajarkan dengan model pembelajaran bervariasi dan minat belajar bervariasi menggunakan media pembelajaran iSpring pada materi kesetimbangan kimia, serta melihat interaksi antara hasil belajar siswa terhadap minat belajar siswa. Populasi dalam penelitian ini adalah seluruh siswa kelas XI MIPA di SMA Negeri 1 Sei Suka yang berjumlah lima kelas. Sampel yang digunakan dalam penelitian ini sebanyak dua kelas diambil dengan cara Purposive Sampling. Sampel dalam penelitian ini yaitu kelas XI MPA 1 sebagai kelas eksperimen 1 yang diberi perlakuan menggunakan model Problem Based Learning (PBL) dan kelas XI MIPA 4 yang diberi perlakuan dengan model Learning Cycle 5E. Uji hipotesis dilakukan dengan ANOVA dua jalur (ANOVA two-way) with General Linear Model (GLM) univariate dengan hasil penelitian pada model pembelajaran yang bervariasi diperoleh harga sig. 0,007 < ð›¼ (0,05) sehingga Ha diterima dan Ho ditolak, dapat disimpulkan bahwa terdapat perbedaan yang signifikan rata-rata nilai hasil belajar siswa pada materi kesetimbangan kimia yang dibelajarkan dengan model pembelajaran bervariasi. Pada minat belajar yang bervariasi diperoleh sig. 0,000 < ð›¼ (0,05) sehingga Ha diterima dan Ho ditolak, dapat disimpulkan bahwa terdapat perbedaan yang signifikan rata-rata nilai hasil belajar siswa pada materi kesetimbangan kimia yang dibelajarkan dengan minat belajar bervariasi. Selanjutnya pada interaksi antara model pembelajaran dan minat belajar diperoleh harga sig. 0,003 < ð›¼ (0,05) sehingga Ha diterima dan Ho ditolak, dapat disimpulkan bahwa terdapat interaksi antara model pembelajaran dengan minat belajar terhadap nilai hasil belajar siswa pada materi Kesetimbangan Kimia.Kata Kunci : Model Problem Based Learning (PBL), Model Learning Cycle 5E, Minat Belajar, Media iSpring, Hasil Belajar, Kesetimbangan Kimia